Konflik Pernikahan Beda Agama Dalam Undang-Undang Dalam Pasal 28 B Ayat 1 UUD 1945 dan Perspektif Hukum Islam - Chandra devaraihan wahyudi; Tajul Arifin (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Interfaith marriage is a complex and sensitive issue in Indonesia, presenting a conflict between positive law and religious values. Article 28 B of the 1945 Constitution guarantees freedom of religion, but its implementation is constrained by unclear regulations and different interpretations. Islamic law, as a source of law, provides a unique view on interfaith marriage, emphasizing individual rights and the principle of justice. To resolve this conflict, a holistic approach that integrates positive law and Islamic law is needed, as well as concrete steps such as the establishment of clear regulations, improvement of public understanding, capacity of legal officials, individual protection systems, interfaith dialogue, interfaith cooperation, and active community participation. Thus, it is expected to create a harmonious, inclusive and equitable marriage environment.